Prevenção do câncer do colo de útero: conhecimento, atitude e prática das mulheres atendidas no ambulatório de um Centro de Assistência de Alta Complexidade em Oncologia - FALCÃO, Bruna Caroline Silva (2022)
Cervical cancer (CCU) is an important public health problem in the world and ranks third among the most common neoplasms among women. It is responsible for 311,000 deaths per year, being the fourth most frequent cause of cancer death in women. Studies show a deficiency of knowledge, attitude and practice of women in relation to the prevention of CC, through this reality, it is necessary to identify the knowledge of women and carry out the early diagnosis of CC. The objective was to analyze the knowledge, attitude and practice of women treated at the outpatient clinic of a CACON on the prevention of cervical cancer. This is a cross-sectional Knowledge, Attitude and Practice (KAP) evaluative study with a quantitative approach, carried out with 246 women, in an oncology referral outpatient clinic in São Luís - MA, from June to September 2021. using a validated and adapted questionnaire, containing sociodemographic questions and the CAP survey, for data analysis, the statistical program IBM SPSS Statistics 22 (2013) was used. The study was submitted to the Research Ethics Committee (CEP) of the Federal University of Maranhão, through Plataforma Brasil, where it obtained a favorable opinion, opinion number: 4,754,076. Of the 246 women, in terms of knowledge, 88.6% had already heard about CC prevention, 51.6% through health professionals, 54.9% had never participated in educational activities regarding CC prevention, 71.5% knew that the Pap smear was used to prevent cervical cancer and 44.3% answered that they performed it annually; when asked about the care needed before performing the Pap smear, 48.8% responded that they had not had sexual intercourse 24 hours before performing the test. Regarding attitude, 48.8% of the women went for the exam to know how their health is, 23.6% had undergone the exam in the last year, 55.3% had no change in the result of the last exam and of those who had alteration, 91.5% underwent treatment. Regarding practice, 78.5% of the women returned to receive the test result, of which 90.9% showed the result to a health professional. Most were between 30 and 39 years old, were married, had completed high school, did not work outside the home and lived close to the health center. A significant association (p<0.05) was found between knowledge, attitude and practice in relation to CCU; and between attitudes and practice in relation to the CCU. The greater the knowledge, the greater the probability of women having positive attitudes towards CC prevention and the greater the probability of having adequate practices in relation to the prevention of that cancer. It is noteworthy that the investigation was of paramount importance to support health professionals to implement preventive actions aimed at improving women's knowledge about cervical cancer prevention.